2015
DOI: 10.5352/jls.2015.25.12.1362
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Cryopreservation Stability of Kimchi Duruchigi Supplemented with Rubus coreanus Miquel Extract

Abstract: The goal of this study was done for evaluating stability according to low-temperature storage of kimchi duruchigi supplemented with a hot water extract of Rubus coreanus Miquel (RCM). Total polyphenol and flavonoid contents in the RCM extract prepared from the hot water were detected by 293.34 μg CA/mg and 90.57 μg quecetin/mg, respectively. DPPH and superoxide radical scavenging activities of the extract were showed by relatively high values of 70.63 and 57.87%, respectively. Kimchi duruchigi was designed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These findings were similar to those reported previously, which showed that the antioxidant effects of kimchi and KS were enhanced by adding antioxidant ingredients. Specifically, the DPPH-scavenging ability of kimchi supplemented with cultured wild ginseng roots improved, as did the phenolic compound, DPPH, and nitric oxide scavenging activities of tofu supplemented with KS [25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were similar to those reported previously, which showed that the antioxidant effects of kimchi and KS were enhanced by adding antioxidant ingredients. Specifically, the DPPH-scavenging ability of kimchi supplemented with cultured wild ginseng roots improved, as did the phenolic compound, DPPH, and nitric oxide scavenging activities of tofu supplemented with KS [25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, as these synthetic food additives are suspected to be carcinogenic, consumers are eager to reduce the use of synthetic food additives in the meat industry (Namiki, 1990). Therefore, the use of natural food additives for the food industry is advantageous because it is a natural product that does not require multiple safety tests before use (Yang, et al, 2015).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%